A case study on the role of project-based learning in improving university students’ speaking skills: From theory to practice - Trihn, Nguyen Thi Tu; Schmitt, Elena (Konińskie Studia Językowe, 2020)
The aims of this paper are twofold: (1) to study the application of project-based learning ten-step process framework suggested by Alan and Stoller (2005) to boost English speaking ability of undergraduate students at the University of Da Nang, and (2) to investigate the levels of undergraduate students’ satisfaction. The subjects were 24 final year undergraduate engineering students at the university of Da Nang during the first semester of the 2019/2020 academic year. The instruments used in this experiment included lesson plans, a project evaluation form, a student’s self-assessment form, a satisfaction questionnaire and interviews
Keywords: English speaking skills; dept.wll; peer-reviewed; project-based learning; self-assessment

儿童与战争: 童年回忆和西班牙内战研究 = Children and the war - Weng, Miaowei (中国社会科学出版社, 2020)
本书将儿童,童年回忆和西班牙内战联系在一起,提出了"佛朗哥儿童"这个新概念.在童年研究和历史回忆研究的二元框架下,作者分析了"佛朗哥儿童"在西班牙20世纪后半叶至今的代表性文学影视作品,以此揭示出儿童在西班牙政治中的重要性,并呈现了西班牙近几十年来的历史和文化走向
OCLC: 1343566654
Keywords: Wen xue yan jiu Xibanya; dept.wll

Cine Politico en Mexico (1968-2017) - Hernandez Rodriguez, Rafael (Latin Americanist, 2020)
WOS:000605954800006
Keywords: dept.wll; peer-reviewed; ⛔ No DOI found

Redemptive children and historical memory: Luis mateo díez’s la gloria de los niños (2007) - Weng, Miaowei (Bulletin of Spanish Studies, 2020)
This article explores contemporary Spanish writer Luis Mateo Díez’s 2007 novel, La gloria de los niños, focusing on the construction of a redemptive child who mends the broken world and keeps alive historical memory. The author looks beyond one single nation state in his reconstruction of children and childhood under the Franco regime. Hidden behind his approach to the reconstruction of the ‘glorious children’ under Franco emerges, on the one hand, his dissolution of any authoritative version of Franco-era children and, on the other, his broader vision and desire to examine Spain and Spanish historical memory in a global context. © 2020 Bulletin of Spanish Studies.
0 citations (Crossref) [2023-10-31] tex.ids: wengRedemptiveChildrenHistorical2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85095847122 type: Article
Keywords: Childhood under Franco; Historical Memory; La gloria de los niños; Ladri di biciclette (1948); Luis Mateo Díez; Post Civil War period; Redemptive Child; Vittorio de Sica; Walter Benjamin; dept.wll; peer-reviewed